Morphology and microbiota of broilers fed diets containing essential oils: review (Research, Society and Development, 2020)
In the current context, students, researchers and professionals working in the poultry sector are looking for alternatives to the use of growth-promoting antimicrobials since the use of these drugs has suffered partial and total restrictions worldwide, a fact that has forced the production sector to renew itself for do not lose participation in the consumer market. Among the main reasons for the removal of antimicrobials in poultry feed are the presence of residues in the feed, its disposal and environmental pollution and the risk of microorganisms extremely resistant to these products, which can cause enormous future difficulties in combating both in the sphere of animal production and in that of human health. The active principles of the various food, medicinal and wild plants, when transformed into essential oils, have been gradually better known and used in this attempt to replace traditional growth promoters without losing their productive capacity. However, because they are a very heterogeneous group with regard to their compositions, the results of this supplementation are still extremely variable and uncertain in relation to the levels of inclusion and interactions with each other. The objective was to discuss the effects of essential oils to replace antibiotics in poultry feed, and their consequences on intestinal morphology, composition of the microbiota and productive performance of broilers.